Molecular Nevogenesis - Andrew L. Ross; Margaret I. Sanchez; James M. Grichnik (Dermatology Research and Practice)
Despite recent advances, the biology underlying nevogenesis remains unclear. Activating mutations in NRAS, HRAS, BRAF, and GNAQ have been identified in benign nevi. Their presence roughly correlates with congenital, Spitz, acquired, and blue nevi, respectively. These mutations are likely to play a critical role in driving nevogenesis. While each mutation is able to activate the MAP kinase pathway, they also interact with a host of different proteins in other pathways. The different melanocytic developmental pathways activated by each mutation cause the cells to migrate, proliferate, and differentiate to different extents within the skin. This causes each mutation to give rise to a characteristic growth pattern. The exact location and differentiation state of the cell of origin for benign moles remains to be discovered. Further research is necessary to fully understand nevus development given that most of the same developmental pathways are also present in melanoma.